Evaluation of the Potential Use of a Collagen-Based Protein Hydrolysate as a Plant Multi-Stress Protectant - Ambrosini, Stefano; Sega, Davide; Santi, Chiara; Zamboni, Anita; Varanini, Zeno; Pandolfini, Tiziana (Frontiers in Plant Science, 2021)
Protein hydrolysates (PHs) are a class of plant biostimulants used in the agricultural practice to improve crop performance. In this study, we have assessed the capacity of a commercial PH derived from bovine collagen to mitigate drought, hypoxic, and Fe deficiency stress in Zea mays. As for the drought and hypoxic stresses, hydroponically grown plants treated with the PH exhibited an increased growth and absorption area of the roots compared with those treated with inorganic nitrogen. In the case of Fe deficiency, plants supplied with the PH mixed with FeCl3 showed a faster recovery from deficiency compared to plants supplied with FeCl3 alone or with FeEDTA, resulting in higher SPAD values, a greater concentration of Fe in the leaves and modulation in the expression of genes related to Fe. Moreover, through the analysis of circular dichroism spectra, we assessed that the PH interacts with Fe in a dose-dependent manner. Various hypothesis about the mechanisms of action of the collagen-based PH as stress protectant particularly in Fe-deficiency, are discussed.